Analisis Penyebab Rendahnya Minat Belajar Siswa dalam Pembelajaran Seni Rupa Kelas XII SMA YAPI Padang - Zafira Ramadani; Yusron Wikarya (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the factors contributing to students’ low interest in learning visual arts among twelfth-grade students at YAPI Senior High School Padang. Low student participation and limited appreciation for visual arts education at the senior high school level have become significant issues that require serious attention, as they may hinder the development of students’ creativity, aesthetic competence, and artistic expression. The study employed a mixed-methods approach using a concurrent triangulation design. The research participants consisted of twelfth-grade students, arts and culture teachers, and homeroom teachers. Data were collected through observations, interviews, documentation, and questionnaires. Quantitative data were analyzed using percentage analysis, while qualitative data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that students’ low interest in learning was influenced by both internal and external factors. Internal factors included attitudes, motivation, talent, and hobbies, with talent emerging as the dominant indicator at 18.01%. External factors included the learning environment, teachers and instructional strategies, and family background, with family factors showing the highest percentage at 18.79%. These findings were further supported by qualitative data indicating that limited facilities and infrastructure caused the learning process to rely predominantly on lecture-based teaching methods. Therefore, students’ low interest in learning visual arts can be understood as the result of the interaction between internal and external factors.